An experimental study on the corrosion sensitivity of metal alloys for usage in PCM thermal energy storages. (August 2019) - Calabrese, Luigi; Brancato, Vincenza; Paolomba, Valeria; Proverbio, Edoardo
Abstract: The vast majority of renewable energy systems, especially solar ones, include thermal energy storage (TES). TES with phase change materials (PCMs) are now an established technology in several applications, but their commercialization and mass introduction cannot ignore reliability, in terms of service life of components. Among PCMs, salt hydrates are widely used but are potentially corrosive. In the present paper, the corrosion behaviour of three metal alloys (AISI 1050 carbon steel, AA 6061 aluminium and CW024A copper alloys) is investigated with magnesium nitrate hexahydrate molten salt at 120 °C. Contrary to previous studies, the study is not based on visual observation or mass loss, but corrosion sensitivity is instead studied via electrochemical impedance spectroscopy (EIS). The results highlight that good corrosion stability was observed for the aluminium alloy, since no evidence of corrosion phenomena were observed on its surface. However, carbon steel and copper alloys show significant electrochemical activity, together with a large amount of corrosion products, after just a few hours of immersion in the severe environmental conditions. Corrosion mechanisms were proposed by fitting EIS curves with several equivalent circuits, therefore suggesting design approaches for PCM-TES systems. Highlights: The corrosion behaviour of three metal alloys is investigated with magnesium nitrate hexahydrate molten salt at 120 °C. Corrosion sensitivity of metal alloys was studied via electrochemical impedance spectroscopy. Electrochemical impedance spectroscopy fitting modeling approach was applied to evaluate metal degradation over time. Good corrosion stability was observed for the aluminium alloy. Carbon steel and copper alloys show a significant electrochemical activity in this severe environmental condition.